Effect of moxibustion based on Lai's Tongyuan needling technique on retention of urine after stroke - WU, Meng; ZHANG, Huihui; YOU, Lyu; DING, Yao; ZHANG, Run; LI, Zhennan; YE, Meixia (Chinese Journal of Integrative Nursing, 2021)
Objective To investigate the effect of moxibustion based on Lai's Tongyuan needling technique on retention of urine after stroke. Methods Totally 65 stroke patients with retention of urine were randomly divided into the control group (n=32) and observation group (n=33). All patients received comprehensive treatment and nursing care, and those in the observation group were given moxibustion based on Lai's Tongyuan needling technique. The frequency of urination and residual urine volume were recorded, and the effect of intervention was compared between two groups. Results Better outcomes of frequency of urination and residual urine volume were found in the observation group than those in the control group after intervention(P＜0. 05), The overall effective rate was 96. 67%(32/33) in the observation group and 78. 13%(25/32) in the control group, with a significant difference (P＜0. 05). Conclusion The moxibustion based on Lai's Tongyuan needling technique is potentially effective to improve the bladder function of patients with retention of urine after stroke. (目的 观察赖氏通元法艾灸对中风后并发癃闭患者的护理效果。方法 选择中风后并发癃闭的患者65例, 按随机数字表法分为对照组32例和试验组33例, 对照组采用常规治疗与护理, 试验组在对照组基础上采用赖氏通元法艾灸。记录2组患者排尿次数和残余尿量, 评价干预效果。结果 试验组排尿次数、膀胱残余尿量改善情况优于对照组, 差异有统计学意义(P＜0. 01)。试验组总有效率96. 67%(32/33), 高于对照组的78. 13%(25/32), 差异有统计学意义(P＜0. 05)。结论 赖氏通元法艾灸可改善中风后癃闭患者的膀胱功能。)